Crypto Wallet: A Perfect Combination with Blockchain and Security Solution for Banking - Singh Yadav, Nagendra; Kumar Goar, Vishal; Kuri, Manoj (International Journal of Psychosocial Rehabilitation, 2020)
A bank is a financial institution that receives deposits and grants loans to its stakeholders. Finance is a stream of banking that involves settlement and controls the withdrawal and deposits. When a currency in the form of cash is deposited into a bank, it is taken care of by the finance process.E-wallets have become a traditional method of banking these days since we have entered the age of digital banking, with which we can see a number of security loopholes specific to payment gateways, where the hackers steal the money from credit or debit cards by diverting the OTP to themselves. It all starts with a minimum amount, but the impact is bigger when the pertransaction amount is increased by every attempt. The SIM clone is another problem area, which needs to get fixed these days. Using SIM clone, anyone can steal money from a user’s account, if or not you are using online banking.This research paper touches on how effectively the banking system can handle frauds related to transactions by ensuring authenticity with the implementation of the system powered by blockchain.